Rapid Assembly of Oligosaccharides by Using a Hydrophobic Tag-Assisted Liquid-Phase Method - Lu, Dan; Wang, Siyao; Yin, Hongli; Chu, Fengting; Wei, Quhao; Wang, Ping (Synlett, 2020)
A 3,5-didocosyloxybenzyl alcohol tag that was introduced at the anomeric position of the carbohydrate acceptor was applied in the assembly of a pentasaccharide. The intrinsic high solubility in nonpolar solvent and precipitation properties in polar solvent are crucial features of this tag. Thus, rapid and simple precipitation-centrifugation can be conducted throughout the synthetic route at each step to ease work-up and purification processes, and reduce the amount of solvent required. This method provides an efficient, environmental-friendly, and economical approach to synthesize complex oligosaccharides.
Keywords: oligosaccharides; glycosylation; precipitation-centrifugation; liquid-phase; tags